ANALISIS HUBUNGAN BIAYA PRODUKSI KELAPA SAWIT TERHADAP PENDAPATAN PETANI DI DESA PULO BAYU KECAMATAN HUTABAYU RAJA, KABUPATEN SIMALUNGUN ORGANIK - Chris Michael; Posman Marpaung; Fandri Siburian (Universitas Quality, 2020)
The aim of study is to 1) determine the productivity of oil palm in the study area, 2) determine the income of oil palm farming in the study area and 3) determine the relationship of the cost of oil palm production with the income of oil palm farmers in the study area. This research was conducted in Pulo Bayu village, Hutabayu Raja district, Simalungun regency. The population in this study were farmers who worked on oil palm plants in Pulo Bayu village with a field area ranging from 0.5-10 Ha and the age of the plants between 3.5-18 years. The number of samples in this study were 30 oil palm farmers. Data analysis was performed descriptively and using simple linear regression analysis. The result showed that the productivity of oil palm plants in the study area was classified as low. The production of oil palm farming in the study area is 82,342.80 kg/year or 1,744.76 kg/ ha (1.75 tons/ha/month). This is lower than the average CPO productivity of smallholder estates 2.5 tons/ ha/month. Net income of oil palm farmer in the study area is Rp 1,308,973.06/ha/month is classified as low because it is lower than the UMR of Simalungun regency (Rp 2,224,036.00/ month). Farming production costs significantly have a positive linear effect on the income of oil palm farmers in the study area.